Moon Knight - MacKay, Jed, 1983- (Marvel Worldwide, Inc., 2021)
"His mission is justice! The mysterious Mr. Knight has opened his Midnight Mission, sheltering his people from the weird and horrible. The Moon Knight stalks the rooftops and alleys marked with his crescent moon tag, bringing violence to any who would harm his flock. While Khonshu languishes in prison, Marc Spector's sacred duty must still be observed: the protection of those who travel at night. But what happens when those he would save are turned into weapons against him? When gangs of elderly residents leave a trail of bizarre violence, Moon Knight must put his body, mind and very soul on the line to end the carnage! A mysterious foe attacks from an unexpected direction, an old friend comes to visit and Marc finds himself answering the same question over and over again: "Why do you wear the mask?""--